1976
DOI: 10.1136/sti.52.5.296
|View full text |Cite
|
Sign up to set email alerts
|

A new look at the serology of treponemal disease.

Abstract: IntroductionThe changes that have recently taken place in the serology of treponemal disease have fortunately tended to make the subject less complicated and more rational than it was in the past; the change that has contributed most of all to this simplification is the widespread adoption of specific antibody tests, in place of the older non-specific ones, in routine testing. To explain how this change has altered the serodiagnosis of treponemal infection it is necessary to discuss briefly syphilis antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
(1 reference statement)
1
10
0
Order By: Relevance
“…In this study, we have tried to delineate the immunological factors better by using a combination of tests for lipoidal The results obtained were generally consistent and pointed strongly to certain conclusions. In a recent study, O'Neill (1976) obtained similar results with fewer tests. In the present study, apart from the 20 cases of late syphilis, the sera that were negative in the.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, we have tried to delineate the immunological factors better by using a combination of tests for lipoidal The results obtained were generally consistent and pointed strongly to certain conclusions. In a recent study, O'Neill (1976) obtained similar results with fewer tests. In the present study, apart from the 20 cases of late syphilis, the sera that were negative in the.…”
Section: Discussionsupporting
confidence: 52%
“…[3][4][5][6][7][8][9] In contrast, Duncan and Kuhn,'°in a similar study using chimpanzees, found that production of specific antitreponemal IgM ceased spontaneously in 10 out of 24 animals who had received no treatment, and treponemal IgM reactivity in sera from patients with late syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…All reactive non treponemal test like VDRL should be confirmed by treponemal tests like TPHA and even TPHA may be required in some cases who were non-reactive to non treponemal tests based on patient's clinical history and symptoms. 6 So a combination of VDRL and TPHA provides an efficient screening for syphilis.…”
Section: Discussionmentioning
confidence: 99%